(untitled) (Research, Society and Development, 2022)
With the declaration of the Covid-19 pandemic in march 2020 by the World Health Organization, government measures were implemented. College Education Institutions had to adapt to the development of academic activities, including in-service practices and Supervised Curricular Internships, making it timely to reflect on the conduct of internships during the pandemic period. Therefore, the present study aimed to analyze the situation of Supervised Curricular Internships, face-to-face courses in the health area in public and private college education institutions in the State of Parana. The research was directed to coordinators and professors who supervise internships of the courses, through a questionnaire with closed and open questions. The answers showed the position of most institutions in not considering the adoption of the internship remotely during the pandemic period. It was evidenced that the undergraduate courses of public and private institutions in the field of health, located in the State of Parana, were affected by the pandemic, especially in the practical experience, provide by the Supervised Curricular Internships.